Vascular and extravascular findings on magnetic resonance angiography of the thoracic aorta and the origin of the great vessels. Issue 4 (18th December 2013) - Sohns, Jan M.; Staab, Wieland; Menke, Jan; Bergau, Leonard; Dabir, Darius; Schwarz, Alexander; Spiro, Judith E.; Dorenkamp, Marc; Harrison, James L.; Steinmetz, Michael; Lotz, Joachim; Sohns, Christian
<x xml:space="preserve">Abstract</x> Purpose To investigate the presence of relevant vascular and incidental extravascular findings in patients undergoing magnetic resonance angiography (MRA) of the thoracic aorta and origin of the great vessels. Materials and Methods In all, 165 consecutive patients (mean age 61 ± 12 years) underwent 1.5 T MRA of the thorax. Two researchers identified vascular and incidental extravascular findings. Clinically relevant vascular findings were defined. Extravascular findings were categorized as minor (Group A, without change in patient treatment), intermediate (Group B, unclear clinical relevance, requiring additional investigations), and major (Group C, causing a change in patient treatment). Results A total of 306 relevant vascular findings were found in our cohort. A total of 397 extravascular findings were observed among the patients and were classified as Group A findings in 81.9% (325/397 findings, observed in 146 of 165 patients), as Group B findings in 15.4% (61/397 findings, observed in 52 of 165 patients), and as Group C in 2.8% of findings (11/397). The clinically relevant Group C findings were observed in 6.7% of patients (11/165), comprising eight previously unknown neoplasms (4.8% of 165), two patients with hemodynamically relevant pericardial effusion (1.2% of 165), and one patient with spondylodiscitis (0.6% of 165) detected by MRA. Conclusion Relevant vascular and extravascular findings were found in patients referred for thoracic MRA. Most extravascular findings can be categorized by MRA as minor, while others required further diagnostics since they may be malignant or otherwise clinically relevant. J. Magn. Reson. Imaging 2014;40:988–995. © 2013 Wiley Periodicals, Inc.